PENGARUH SUHU DAN LAMA PEMANASAN TERHADAP PEMBENTUKAN AKRILAMIDA PADA PEMBUATAN MINYAK KELAPA DENGAN CARA PANAS - PANGIHOTAN NAPITUPULU, TOGA
Acrylamide had been detected as contaminant in food products prepared at high temperature. The paper describes an analytical method development for the analysis of acrylamide in coconut oil and an experiment to investigate the influences of temperature and heating time on acrylamide formation in the production coconut oil using thermal method. Acrylamide was identified and quantified by High Performance Liquid Chromatography (HPLC) method. Under following conditions : a mixture of phosphoric acid solution pH 2.50 and acetonitrile (95:5) as mobile phase, a Phenomenex(R) coloumn C18-RP (300 x 3.90 mm, 10 um) at room temperature, a UV detector at 210 nm, and a Hitachi D-7000 chromatograph, acrylimide was eluted at 7.64 minutes. The method gave a relative standar deviation (RSD), precentage of recovery, correlation coefficient (r), and regression variation coefficient (Vxo) values of respectively 1.66% for acrylamide at the concentration level of 0.4 ug/mL, 95.81% at the concentration level of 1.4974 ug/mL, 0.997 at the concentration range of 0.2-1.6 ug/mL, and 3.76%. Furthermore, the method gave the limit of detection and limit of quantification for acrylamide of respectively 0.06 and 0.18 ug/mL. The method was applied for the analysis of acrylamide formed during the production of coconut oil in this research. Coconut oil was formed at varied heating temperature, ie 90oC, 100oC, and 110oC, and varied heating time, ie 15, 25, dan 35 minutes, respectively. The acrylamide content in coconut oil was not detected at heating temperature of 90oC and 100oC after heating time of 15 minutes; but was found to be (ug/kg) 82.81 + 16.83 at 100oC after heating time of 25 minutes, 256.63 + 7.06 at 100oC after heating time of 35 minutes, 181.33 + 5.96 at 110oC after heating time of 15 minutes, 199.13 + 14.78 at 100oC after heating time of 25 minutes, and 336.30 + 16.57 at 110oC after heating time of 35 minutes, respectively. The formation of acrylamide was increased with increament in temperature and heating time.